2009
DOI: 10.1590/s0102-86502009000300009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lidocaine and racemic bupivacaine on neuromuscular blockade produced by rocuronium: a study in rat phrenic nerve-diaphragm preparation

Abstract: PURPOSE: To evaluate in vitro lidocaine and racemic bupivacaine effects in neuromuscular transmission and in neuromuscular blockade produced by rocuronium. METHODS: Rats were distributed in 5 groups (n = 5) in agreement with the studied drugs: lidocaine, racemic bupivacaine, rocuronium, separately (Groups I, II, III); rocuronium in preparations exposed to local anesthetics (Groups IV, V). The concentrations used were: 20 µg/mL, 5 µg/mL and 4 µg/mL, for lidocaine, bupivacaine and rocuronium, respectively. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
0
13
1
7
Order By: Relevance
“…The study of MEPPs is important to investigate the presynaptic effects of the drugs used, due to its interference in mediator release 22 . In contrast to previous reports on lidocaine [4][5]21 , describing that it initially increases MEPP frequency, the local anesthetics used in the study caused a progressive decrease both in the frequency and amplitude of these potentials until complete blockade.…”
Section: Discussioncontrasting
confidence: 69%
“…The study of MEPPs is important to investigate the presynaptic effects of the drugs used, due to its interference in mediator release 22 . In contrast to previous reports on lidocaine [4][5]21 , describing that it initially increases MEPP frequency, the local anesthetics used in the study caused a progressive decrease both in the frequency and amplitude of these potentials until complete blockade.…”
Section: Discussioncontrasting
confidence: 69%
“…5---7,11,13,16---19 A concentração de ropivacaína empregada foi estabelecida em projeto piloto e determinada a partir de dados apresentados em estudos realizados em nosso meio, onde foram utilizados outros anestésicos locais amino--amidas com características semelhantes à ropivacaína. 6,7 Matsuo et al, 13 em preparação semelhante à utilizada neste estudo, avaliaram a associação de d-tubocurarina com diferentes anestésicos locais, e observaram que mesmo em concentrações ineficazes, os anestésicos locais potencializaram o bloqueador neuromuscular, evidenciado pela diminuição significativa da ED50. Em relação à influên-cia dos bloqueadores neuromusculares nos efeitos dos anestésicos locais, estes autores também descreveram que concentrações ineficazes de d-tubocurarina causaram similar diminuição da ED50 e aumento na potência dos anestésicos locais.…”
Section: Discussionunclassified
“…5---7,11,13,16---19 The ropivacaine concentration used was established in a pilot study and determined from data presented in studies carried out in Brazil, where other amino-amide local anesthetics with similar characteristics to ropivacaine were used. 6,7 Matsuo et al 13 evaluated, in preparation similar to that used in this study, the association of d-tubocurarine with different local anesthetics and found that, even in ineffective concentrations, local anesthetics potentiated neuromuscular blocker, as evidenced by significant decrease in the ED50. Regarding the influence of neuromuscular blockers on the effects local anesthetics, these authors also reported that ineffective concentrations of d-tubocurarine caused a similar decrease of ED50 and increase of local anesthetic potency.…”
Section: Discussionmentioning
confidence: 92%